CONCEPTS OF PHYSICS Quantities and units - Hening Hendrato (JAKSTIK Journal, 2006)
Physics as a branch of science requires a lot of measurements such as measuring the length, mass, time, and others. By understanding basic physics concepts such as the concept of expected quantities and units will not be much difficulty when they have to solve problems related to mathematical physicists. It is expected that this concept can bridge between macro- physics of the universe of knowledge to small objects that can only be viewed with a microscope. As a supporter in a discussion of this topic, expected definitions bekaitan understanding of physics concepts about quantities and units.